KONSEP PENDIDIKAN ISLAM DALAM BERBAGAI PERSPEKTIF - Faishal (el Hakim Press, 2019)
Unequal levels of religious understanding cause different views, attitudes, behaviors and forms of different teachings practice. Among the causes of lack of understanding are the back ground of education that has been followed, as we know in our country in general there are education based on religion (like madrasah and pesantren) and education based on non-religion. It?s okay we are not comparing between schools that are based on religion and general, but between schools based on religion itself the patterns are very different. So, this is where we need to look again at the concept of Islamic education, the basis of its references and the objectives of Islamic education. Through this paper, the author presents various concepts that have been offered by Islamic education experts, both classical and contemporary, so that we can realize and apply how Islamic education as a whole.